The transformation : discovering wholeness and healing after trauma - Gordon, James S. (James Samuel) (HarperOne, an imprint of HarperCollinsPublishers, 2019)
In his role as the founder and director of The Center for Mind-Body Medicine (CMBM), the worlds largest and most effective program for healing population-wide trauma, Harvard-trained psychiatrist James Gordon has taught a curriculum that has alleviated trauma to populations as diverse as refugees and survivors of war in Bosnia, Kosovo, Israel, Gaza, and Syria, as well as Native Americans on the Pine Ridge Reservation in South Dakota, New York city firefighters and their families, and members of the U. S. military. Dr. Gordon and his team have also used their work to help middle class professionals, stay-at-home mothers, inner city children of color, White House officials, medical students, and people struggling with severe emotional and physical illnesses. The Transformation represents the culmination of Dr. Gordon<U+2019>s fifty years as a mind-body medicine pioneer and an advocate of integrative approaches to overcoming psychological trauma and stress. Offering inspirational stories, eye-opening research, and innovative prescriptive support, The Transformation makes accessible for the first time the methods that Dr. Gordon<U+2014>with the help of his faculty of 160, and 6,000 trained clinicians, educators, and community leaders<U+2014>has developed and used to relieve the suffering of hundreds of thousands of adults and children around the world.